2017
DOI: 10.1016/j.bpj.2016.11.3205
|View full text |Cite
|
Sign up to set email alerts
|

Drunken Membranes: Short-Chain Alcohols Alter Fusion of Liposomes to Planar Lipid Bilayers

Abstract: Although the effects of ethanol on protein receptors and lipid membranes have been studied extensively, ethanol's effect on vesicles fusing to lipid bilayers is not known. To determine the effect of alcohols on fusion rates, we utilized the nystatin/ergosterol fusion assay to measure fusion of liposomes to a planar lipid bilayer (BLM). The addition of ethanol excited fusion when applied on the cis (vesicle) side, and inhibited fusion on the trans side. Other short-chain alcohols followed a similar pattern. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 81 publications
(117 reference statements)
3
23
1
Order By: Relevance
“…Ethanol is also reported to reduce the transition temperature of lipid bilayers (through promoting bilayer disorder) and at high concentrations can cause lipid interdigitation [39,40]. This disordering effect is not restricted to ethanol, and all three of the alcohols used within our studies had a bilayer disordering effect [41]. Thus, during the production of liposomes, the miscible alcohols present during the mixing process may reduce the transition temperature of the bilayer discs, hence increasing their elasticity and promoting vesicle formation.…”
Section: Discussionmentioning
confidence: 52%
“…Ethanol is also reported to reduce the transition temperature of lipid bilayers (through promoting bilayer disorder) and at high concentrations can cause lipid interdigitation [39,40]. This disordering effect is not restricted to ethanol, and all three of the alcohols used within our studies had a bilayer disordering effect [41]. Thus, during the production of liposomes, the miscible alcohols present during the mixing process may reduce the transition temperature of the bilayer discs, hence increasing their elasticity and promoting vesicle formation.…”
Section: Discussionmentioning
confidence: 52%
“…Application of short-chain alcohols was reported to facilitate hemifusion/fusion of liposomes in reduced protein-free systems by altering membrane properties ( Chanturiya et al, 1999 ; Paxman et al, 2017 ). Here, we introduced low concentrations (2%) of methanol (MeOH) into cells via the patch pipette and characterized potential changes of secretion properties in Ca 2+ -uncaging experiments.…”
Section: Resultsmentioning
confidence: 99%
“…Some examples of small foreign molecules include cholesterol, fatty acids, and alcohols, systems that partition differently between the membrane phases and the aqueous environment. The latter have attracted a great deal of attention since they display a wide spectrum of physiological and pharmacological actions such as metabolism, membrane fusion, alcohol toxicity, and general anesthesia [1,2,3,4,5]. In particular, much research has been devoted to the study of lipids–alcohols interactions to elucidate the mechanisms of anesthesia.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to GUVs formed in the presence of ethanol, GUVs preformed in water with subsequent ethanol addition exhibit different shape and phase transition temperatures. Furthermore, a recent capacitance study showed that alcohols alter fusion of small liposomes to planar lipid bilayers by enhancing the energy barrier for vesicle fusion, likely through an increase in membrane fluidity due to the presence of alcohol [2].…”
Section: Introductionmentioning
confidence: 99%